Perceptions of university students on the presence of stray cats on campus: benefits, issues, and management strategies - Affendy Lee, Noor Azli; Abd Ghani, Kay Dora; Rozli@Rosli, Mohd Ikmal Fazlan; Zaini, Intan Rabiatulainie (Universiti Teknologi MARA, Kedah, 2024)
The study investigates the perceptions of university students regarding the presence of stray cats on campus. The primary objective is to understand their attitudes towards stray cats and the perceived benefits and issues they bring to the university environment. The methodology involved surveying students from various faculties from a campus in UiTM, collecting data on their awareness, attitudes, and experiences with stray cats. The survey included questions on whether students felt stray cats positively or negatively impacted the campus, their concerns about public health, and their support for university initiatives to manage or adopt these animals. Results indicate a diverse range of opinions. Many students appreciate the presence of stray cats, associating them with a unique and positive campus environment. There is significant support for humane management programs such as Trap-Neuter-Return (TNR) and for providing food and shelter for the cats. However, there are also concerns about health risks and the potential for stray cats to cause disturbances. In conclusion, while the presence of stray cats is largely seen as beneficial by the student body, there is a clear need for structured management and welfare programs. Implementing educational campaigns and collaborating with local animal organizations can enhance the wellbeing of both the cats and the campus community. This study highlights the importance of balancing animal welfare with public health and campus harmony.